Effects of inoculation against a disinformation campaign: A case study of disinformation over Japan's release of Fukushima treated water - John Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2024)
This study examines whether news media can effectively counter a disinformation campaign. It uses disinformation against the release of treated water from the Fukushima nuclear power plant in Japan as a case study from the perspective of media studies. Based on psychological inoculation theory and multivariate statistical analysis of survey data collected in Feb 2024, it is found that warnings about a disinformation attack from the news media can reduce people's beliefs in actual disinformation. However, the results also reveal that news media reports on debunked disinformation can have the opposite effect unless they also educate people with tropes used in the debunked disinformation.
Keywords: 330; Disinformation campaign; inoculation theory; media literacy